'Don't Change the Hardware, but the Activities': Emerging Forms of Political, Moral, and Ethnic Heritage Consumption in Seoul, South Korea. (3rd May 2020) - Silcott, William
ABSTRACT: The 2008 burning of South Korean National Treasure No. 1, Namdaemun Gate and its 2013 reopening served as central events in local reevaluations of the cultural value of historical sites. Based on interviews and ethnographic observations conducted in Seoul during 2014, this paper examines the ways the consumption of history is understood and negotiated by stakeholders and visitors. It finds that while most Seoulite visitors framed site visits as banal park trips, the historical significance of these spaces simultaneously made trips a moral and political obligation. Responsibility to consume history becomes explicit in Korean citizens' accusations of their fellow citizens' failure to participate in acts of remembering. At the same time, the administration of these sites reinforces and facilitates widespread heritage consumption, as seen in their efforts to package the past and draw in domestic and international consumers. These negotiations and contestations are here understood, following Fredrik Barth, as material and cultural assets employed in granting access to forms of capital and evaluating ethnic identity. The consumption of history becomes the duty of Koreans in which leisure activities and ethnic obligations are enhanced through reflections on globalization through international visitors, national events, and the historical discourses surrounding the sites themselves.